An Effective Way of Producing Fully Assembled Antibody in Transgenic Tobacco Plants by Linking Heavy and Light Chains via a Self-Cleaving 2A Peptide - Lin, Yuan; Hung, Chiu-Yueh; Bhattacharya, Chayanika; Nichols, Starr; Rahimuddin, Hafsa; Kittur, Farooqahmed S.; Leung, TinChung; Xie, Jiahua (Frontiers in Plant Science, 2018)
Therapeutic monoclonal antibodies (mAbs) have evolved into an important class of effective medicine in treatment of various diseases. Since the antibody molecule consists of two identical heavy chains (HC) and two light chains (LC), each chain encoded by two different genes, their expressions at similar levels are critical for efficient assembly of functional recombinant mAbs. Although the plant-based expression system has been tested to produce fully assembled recombinant mAbs, coordinately expressing HC and LC at similar levels in a transgenic plant remains a challenge. A sequence coding for a foot-and-mouth disease virus (FMDV) 2A peptide has been successfully used to link two or more genes, which enable the translated polyprotein to be “self-cleaved” into individual protein in various genetically modified organisms. In the present study, we exploited the usage of F2A in Ebola virus monoclonal antibody (EBOV mAb) production. We found that transgenic tobacco plants carrying a transcription unit containing HC and LC linked by 2A not only produced similar levels of HC and LC but also rendered a higher yield of fully assembled EBOV mAb compared to those expressing HC and LC in two independent transcription units. Purified EBOV mAb bound to an Ebola epitope peptide with an apparent Kd value of 141.1 ± 22.6 nM (R²=0.9801), indicating its proper assembly and high affinity binding to Ebola epitope peptide. To our knowledge, this is the first report showing mAb production by overexpressing a single transcription unit consisting of HC, LC and 2A in stable transformed tobacco plants.